Reviews. Issue 2 (1st November 2015) - Turnbull, Paul; McCall, Grant; Mückler, Hermann; Mann, Jatinder; Eddy, Anne; Quanchi, Max; Lowe, John; Smith, Roy; Powell, Debra; Campbell, Maxine; Brooking, Tom; Labrum, Bronwyn; et al.
The Voyagers: Remarkable European Explorations of New Zealand, Paul Moon (2014) Auckland: Penguin Books, 256 pp., ISBN 978 0 1435 7055 4 (pbk), NZ40Intimate St rangers: Friendship, Exchange and Pacific Encounters, Vanessa Smith (2010) Cambridge: Cambridge University Press, 336pp., ISBN 978 0 5217 2878 2 (pbk), £24.99The Atlantic World in the Antipodes: Effects and Transformations since the Eighteenth Century, Kate Fullagar (ed.) (2012) Newcastle upon Tyne: Cambridge Scholars Publishing, 350 pp., ISBN 978 1 4438 3744 6 (hbk), £44.99An Awfully Big Adventure: New Zealand World War One Veterans Tell Their St ories, Jane Tolerton (2013) Auckland: Penguin Books, 304pp., ISBN 978 0 1435 6849 0 (pbk), NZ45New Zealand and the First World War 1914–1919, Damien Fenton with Caroline Lord, Gavin McLean and Tim Shoebridge (2013) Auckland: Penguin Books, 112pp., ISBN 978 0 1435 6975 6 (hbk), NZ75Mihaia: The Prophet Rua Kenana and his Community at Maungapohatu, Judith Binney, Gillian Chaplin, Craig Wallace (2011) Wellington: Bridget Williams Books, 256pp., ISBN 978 1 9271 3130 5 (pbk), NZ49.99Nga Morehu: The Survivors, Judith Binney, Gillian Chaplin (2011) Wellington: Bridget Williams Books, 256pp., ISBN 978 1 9271 3131 2 (pbk), NZ49.99Diminishing Conflicts in Asia and The Pacific: Why Some Subside and Others Don't, Edward Aspinall, Robin Jeffrey and Anthony J. Regan (eds) (2013) London and New York: Routledge, 298 pp., ISBN 978 1 1388 4467 4 (pbk), £29.99New Zealand's China Experience: Its Genesis, Triumphs and Occasional Moments of Less than Complete Success, Chris Elder (ED.) (2012) Wellington: Victoria University Press, 256 pp., ISBN 978 0 8647 3837 0 (hbk), NZ50Mad on Radium: New Zealand in the Atomic Age, Rebecca Priestley (2012) Auckland: Auckland University Press, 296pp., ISBN 978 1 8694 0727 8 (pbk), NZ44.99Peace, Power and Politics: How New Zealand Became Nuclear Free, Maire Leadbeater (2013) Dunedin: Otago University Press, 344pp., ISBN 978 1 877578 58 8 (pbk), NZ55Friendly Fire: Nuclear Politics and the collapse of Anzus, 1984–1987, Gerald Hensley (2013) Auckland: Auckland University Press, 336pp., ISBN 978 1 86940 741 4 (pbk), NZ45Sorrows of a Century: Interpreting Suicide in New Zealand, 1900–2000, John C. Weaver (2014) Wellington: Bridget Williams Books, 449pp., ISBN 978 1 9272 7723 2 (pbk), NZ59.99Childhoods: Growing Up in Aotearoa New Zealand, Nancy Higgins and Claire Freeman (eds) (2013) Dunedin: Otago University Press, 344 pp., ISBN 978 1 8775 7849 6 (pbk), NZ50A New Zealand Book of Beasts: Animals in our Culture, History and Everyday Life, Annie Potts, Philip Armstrong and Deidre Brown (2013) Auckland: Auckland University Press, 336pp., ISBN 978 1 8694 0772 8 (pbk), NZ49.99New Zealand Fashion Design, Angela Lassig with Peter Shand (2010) Wellington: Te Papa Press, 532 pp., ISBN 978 1 8773 8537 7 (hbk), NZ120New Zealand Film and Television: Institution, Industry and Cultural Change, Trisha Dunleavy and Hester Joyce (2011) Bristol: Intellect, 297 pp., ISBN 978 1 8415 0457 5 (pbk), £30Touring the Screen: Tourism and New Zealand Film Geographies, Alfio Leotta (2011) Bristol: Intellect, 208 pp., ISBN 978 1 8415 0475 9 (pbk), £25A Made-Up Place: New Zealand in Young Adult Fiction, Anna Jackson, Geoffrey Miles, Harry Ricketts, Tatjana Schaefer and Kathryn Walls (2011) Wellington: Victoria University Press, 224 pp., ISBN 978 0 864736 97 0 (pbk), NZ40From Manoa to a Ponsonby Garden, Albert Wendt (2012) Auckland: Auckland University Press, 80 pp., ISBN 978 1 8694 0734 6 (pbk), NZ24.99Ancestry, Albert Wendt (2012) Wellington: Huia, 314 pp., ISBN 978 1 7755 0037 7 (pbk), NZ35